2016
DOI: 10.3146/ps15-1.1
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Related Physiological and Metabolic Traits in Peanut Seedlings

Abstract: To maintain high yields under an increasingly hotter climate, high temperature resilient peanut cultivars would have to be developed. Therefore, the mechanisms of plant response to heat need to be understood. The objective of this study was to explore the physiological and metabolic mechanisms developed by virginia-type peanut at early growth stages in response to high temperature stress. Peanut seedlings were exposed to 40/35°C (heat) and 30/25°C (optimum temperature) in a growth chamber. Membrane injury (MI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Similarly, N04074FCT did not recover from either short or prolonged dry conditions in laboratory testing; but GP-VT NC 01 maintained highest TE and A under ambient VPD, and had the greatest stomatal recovery in the field, along with GP-NC WS 17, tested as line SPT 06-07 by Rosas-Anderson et al (2014a) and Shekoofa et al (2015). In other studies, GP-NC WS 17 showed low epidermal conductance, and had minimal changes of the F v /F m ratio and metabolite levels in rainfed vs. irrigated plants and under heat stress (Rosas-Anderson et al, 2014b;Singh et al, 2014Singh et al, , 2016. GP-NC WS 17 line derived from interspecific hybridization with Arachis cardenasii Krapov.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, N04074FCT did not recover from either short or prolonged dry conditions in laboratory testing; but GP-VT NC 01 maintained highest TE and A under ambient VPD, and had the greatest stomatal recovery in the field, along with GP-NC WS 17, tested as line SPT 06-07 by Rosas-Anderson et al (2014a) and Shekoofa et al (2015). In other studies, GP-NC WS 17 showed low epidermal conductance, and had minimal changes of the F v /F m ratio and metabolite levels in rainfed vs. irrigated plants and under heat stress (Rosas-Anderson et al, 2014b;Singh et al, 2014Singh et al, , 2016. GP-NC WS 17 line derived from interspecific hybridization with Arachis cardenasii Krapov.…”
Section: Discussionmentioning
confidence: 94%
“…All of them except SPT 06-07 are released varieties, which are currently under cultivation in the Virginia-Carolina region in the USA. These genotypes were selected for the present study based on their differential responses to heat or drought stress [46][47][48][49] and personal correspondence with peanut breeders/specialists, Balota M. and Isleib T. G. Bailey and Phillips were found to have reduced membrane injury during heat stress 46 . Georgia-12Y has drought tolerance based on gross dollar value return per hectare 49 .…”
Section: Methodsmentioning
confidence: 99%
“…Sugg and Wynne have large pod size, which makes them susceptible to drought stress 48 . SPT 06-07 has been identified as potentially heat tolerant based on metabolic (increased galactinol, reduced hydroxyproline, and higher saturated vs. unsaturated fatty acid ratio) and physiological (lower membrane injury) traits 47 . RT-PCR was performed using gene-specific primers, and in all cases, gene expression results are normalized to the expression of the housekeeping gene Actin-7 (see Supplementary Table S4).…”
Section: Methodsmentioning
confidence: 99%
“…However, six genotypes 796, 55‐437, ICG 1236, ICGV 86021, ICGV 87281 and ICGV 92121 were recovered as heat tolerant based on cellular membrane stability (CMS), crop growth rate and pod growth rate under HS condition (Craufurd et al., ). Similarly, the genotype SPT 06‐07 was reported to be HS tolerant based on lower membrane injury and increased galactinol, reduced hydroxyproline production (Singh, Balota et al., ).…”
Section: Harnessing Genetic Variability For Hs Tolerance In Grain Legmentioning
confidence: 99%